Preschool Age Fundamental Movement Skills Level - Elok Ludyana; Imam Hariadi; Nurrul Riyad Fadhli (CV Rezki Media, 2022)
Background: Teachers and parents need to know and understand the importance of fulfilling motor skills in pre-school-aged children to develop these habits and help reduce the rate of decline associated with motor delays in children's gross motor development. Objectives: This study aims to determine the level of fundamental movement skills of pre-school-age children at PAUD Tunas Bangsa in Bakalan Krajan, Malang City. Methods: This non-experimental study utilizes a descriptive research design with a survey method as its approach. The participants in this study were 15 children aged 3-5 years old from PAUD Tunas Bangsa Bakalan Krajan in Malang City. This study is a population study because all subjects were included in the study. The instrument used to determine the basic movements of pre-school-age children uses TGMD-2 (Test of Gross Motor Development). This study analyzed data using a table of norms for the Test of Gross Motor Development (TGMD-2) and percentages. Results: The study's final findings revealed that the level of fundamental movement or gross motor skills of children aged 3-5 years at PAUD Tunas Bangsa in Malang City showed an average Gross Motor Quotient (GMQ) score of 124, establishing them in the high category. Conclusion: The level of fundamental movement skills of pre-school age children at PAUD Tunas Bangsa Bakalan Krajan in Malang City is in a good category, as evidenced by two measuring indicators, namely locomotor motion, and manipulative motion, so it can be said that children's gross motor skills develop by their level age.